Pengembangan Modul Berbasis Socio-Scientific Issue (SSI) Untuk Meningkatkan Kemampuan Bernalar Ilmiah Siswa SMP - Fira Aulia Annur Rizky (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Science learning not only focuses on mastering concepts, but also on developing students’ scientific thinking skills through the application of scientific methods in daily life. However, junior high school students’ scientific reasoning abilities are still considered low, so innovative and contextual teaching materials are needed. One alternative that can be used is an module based on SocioScientific Issues (SSI), which connects science materials with real-life problems in students’ surrounding environments. This study aimed to describe the validity, practicality, and effectiveness of an SSI-based module in improving junior high school students’ scientific reasoning abilities. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of the stages of analyze, design, develop, implement, and evaluate. The data collection instruments included validation sheets, learning implementation observation sheets, scientific reasoning ability test sheets, and student response questionnaires. Data analysis was conducted using percentage analysis to determine the validity and practicality levels, while the N-gain analysis was used to determine the improvement of students’ scientific reasoning abilities based on pre-test and post-test results. The results showed that the SSIbased module met the valid criteria based on validators’ assessments and demonstrated good practicality in the learning process. Furthermore, the effectiveness analysis indicated an improvement in students’ scientific reasoning abilities with an average N-gain score of 0.42, which was categorized as moderate. Based on these findings, the SSI-based module was declared valid, practical, and effective, so it can be used as an alternative science teaching material to help improve junior high school students’ scientific reasoning abilities.
:: Finalisasi file repositori 20 Juli 2026_Kurnadi
Keywords: module; Socio-Scientific Issue (SSI); scientific reasoning ability